Intifada Diplomatik: Negara-Negara Yang Menentang Israel dan Dampaknya Terhadap Lanskap Politik Global - Mohammad Ilham Fahmi Rusdi; Ulya, Nurul Fikriyatul; Halifah, Nur (Middle Eastern Culture & Religion Issues, 2024)
This article discusses the phenomenon of the "Diplomatic Intifada" within the Israel-Palestine conflict and its impact on the global political landscape. This conflict, which has persisted for over seven decades, has its roots in the establishment of the state of Israel in 1948 and continues to evolve through Palestinian resistance, including two major waves of Intifada from 1987-1993 and 2000-2007. This study employs a literature review methodology with a descriptive-analytical approach, integrating sources from books, journals, and academic articles to provide a comprehensive analysis. The purpose of this study to identifies that the development of the Intifada, from non-violent resistance to militant actions,Palestinian organization resistance, has influenced international support for Palestine and intensified diplomatic pressure on Israel. The research findings indicate that the Intifada has evolved from a non-violent resistance movement to a more militant form of struggle, as reflected in Intifada I (1987-1993) and Intifada II (2000-2005). This development has had significant implications for the political and economic dynamics in the region and has shaped international views and support. The article also examines the role of Palestinian resistance organizations such as Fatah, the PLO, and Hamas, as well as the stance of several countries opposing Israel, including the severing of diplomatic relations by nations such as Iran. The study concludes that the "Diplomatic Intifada" has transformed the global political landscape by increasing international pressure on Israel and reinforcing support for the Palestinian struggle.